Analysing the manipulation of the number of players on tactical, technical, and physical performance in youth futsal - Gomes, S. A.; Travassos, B.; de Oliveira Castro, H.; Clemente, F. M.; Parca, G. M.; Gomes, L. L.; Ferreira, C. E. S. (International Journal of Performance Analysis in Sport, 2024)
The aim of this study was to comprehensively describe and compare the effects of different practice tasks, specifically 4 × 4, 3 × 3, 2 × 2 with goalkeepers (GK) in a 40 × 20 m field court. Forty-two male U17 players (age = 15.62 ± 0.58 years) from three futsal teams participated in the study. The tactical-technical offensive and defensive actions were measured using Videobserver® software. To measure external load (EL) and internal load (IL) during futsal tasks, the WIMU PROTM Ultra-Wideband (UWB) tracking system was used. To compare the tasks, the ANOVA for repeated measures was used. Results revealed that the reduction on the number of players contributed to increase the number of passing and shooting actions, while a generalised increase in physical and physiological responses were observed. In general, the major differences were observed between GK + 2 × 2 + GK and GK + 3 × 3 + GK in relation to GK + 4 × 4 + GK while some differences in physical and tactical-technical actions were also observed between GK + 2 × 2 + GK and GK + 3 × 3 + GK. Thus, the reduction on the number of players in large games can be considered a pedagogical strategy to promote an increase in the tactical-technical actions, such as passing and shooting actions, increasing the physical intensity of players.